Pengatur Suhu Otomatis Pada Solar Water Heater Berbasis IoT - Rosiana, Elfirza; Abdurahman, Abdurahman; Gunastuti, Dwi Anie; Aditya, Sugeng (Forum Kerjasama Pendidikan Tinggi, 2022)
Humans in everyday life really need energy. Energy use is expected to be sustainable, safe and clean. Solar is a renewable energy source that sustains life on earth, it can be utilized through photovoltaic and solar thermal systems. Solar thermal systems that capture solar energy can be used directly for water heating purposes. So that an environmentally friendly water heater can be created. This water heater is a solar water heater. Another problem is that the temperature setting for hot water is still manual, causing waiting time and wasted energy when mixing water is not according to your wishes and needs. The solution requires an automatic temperature regulator is needed on a solar water heater. The DS18B20 temperature sensor is used to read the water temperature, the Wemos D1 R2 microcontroller will consider whether the temperature read is appropriate or not according to the user wishes. If it is not suitable, it will instruct the relay to be active and turn on the water pump to circulate water to the heating collector. Setting the desired temperature can be done remotely using Internet of Things technology. From the results of testing the tool, the solar water heater that has been made is capable of providing hot water temperatures of 50.25 °C, 46°C, 43.12 °C when the tank contains 10 liters, 20 liters and 30 liters of water. The set point setting was successfully done using the blynk platform